Applicability of theory of reasoned action in Malaysian Islamic Banking Institutions - Mohd Ali, Hafizi; Shaari, Rohaya; Ahmad, Abd Halim @ Hamilton (Universiti Sains Islam Malaysia, 2005)
Internet has changed the way business is conducted and one of the emerging uses of the Internet is for banking transaction.With an increasing affluent community, the potential of Internet banking cannot be ignored. The purposed of this paper is to test the applicability of the Theory of Reasoned Action (TRA) in predicting the intention to bank online among Islamic banks’ customers.A structured questionnaire was used to elicit information from the customers using a convenience sampling techniques.A total of 82 responses were received.The findings indicate that the Theory of Reasoned Action (TRA) is valid model in predicting the intention to bank online.Attitude (2=0.565,p<0.01) and subjective norm (2=0.211, p<0.01) were found to be positively related to intention with the former being the more influential predictor. Subjective norm also positively influences. (2=0.373, p<0.01) the attitude to bank online.